Rescue Antenatal Corticosteroids in Late Preterm Birth after Completion of the Initial Cycle of Antenatal Corticosteroids during the Early Preterm Period - Da Eun Jeong; Jung Yun Lee; Eun Ji Oh; Kyong-No Lee; Hyunsu Kim; Hyeon Ji Kim; Jee Yoon Park; Young Hwa Jung; Kyung Joon Oh; Chang Won Choi (Clinical and Experimental Obstetrics & Gynecology)
Background: Late preterm birth is associated with increased risks of adverse neonatal outcomes, including respiratory distress syndrome (RDS) and hypoglycemia. The use of antenatal corticosteroids (ACS) has been shown to reduce these risks in early preterm infants. However, the efficacy of rescue ACS in late preterm infants remains uncertain. This study aimed to assess the effectiveness of rescue ACS in reducing the incidence of RDS and hypoglycemia in late preterm infants. Methods: A retrospective cohort study was conducted on women who delivered singleton late preterm infants (34 + 0 to 36 + 6 weeks of gestation) at a tertiary hospital. The inclusion criteria were completion of the initial cycle of ACS in the early preterm period (before 34 + 0 weeks of gestation). Data on maternal baseline characteristics, ACS administration, and neonatal outcomes were collected from medical records. Statistical analyses, including logistic regression and multivariate modeling, were performed to assess the association between rescue ACS and neonatal outcomes. Results: A total of 155 singleton late preterm infants were included in the study. Among them, 27.8% (43/155) received rescue ACS after 34 weeks of gestation, while 72.2% (112/155) did not. Neonates who did not receive rescue ACS had a significantly higher incidence of RDS compared to those who did (10.7% vs. 0%, p = 0.038). However, the results were not statistically significant in the multivariate analysis (odds ratio (OR), 0.07; 95% confidence interval (CI), 0.00–1.48; p = 0.087). Additionally, there were no significant differences in the frequencies of hypoglycemia (glucose level ≤40 mg/dL) (8.0% vs. 9.3%, p = 0.755) and hypoglycemia (glucose level ≤60 mg/dL) (52.7% vs. 37.2%, p = 0.106) between the two groups. Conclusions: Rescue ACS administration in late preterm infants was not associated with a reduced risk of RDS. Additionally, there was no significant difference in the incidence of hypoglycemia. Further studies with larger sample sizes are needed to confirm these results and assess potential long-term implications.